A three-component model of the spinal nerve ramification: Bringing together the human gross anatomy and modern Embryology - Homma, Shunsaku; Shimada, Takako; Wada, Ikuo; Kumaki, Katsuji; Sato, Noboru; Yaginuma, Hiroyuki (Frontiers in Neuroscience, 2023)
Due to its long history, the study of human gross anatomy has not adequately incorporated modern embryological findings, and consequently, the current understanding has often been incompatible with recent embryological findings. For example, the traditional epaxial and hypaxial muscle distinction, and their corresponding innervation by the dorsal and ventral rami of the spinal nerve, does not correspond to the two global embryonic domains defined by the mesodermal lineages of target tissues. Here, we report a hypothetical model of the spinal nerve ramification, which is compatible with the contemporary embryological findings, and provide some evidence to support it. Our theoretical model brings a novel view of the body wall organization, which can also explain the comprehensive reasoning for the genesis of diverse branching patterns. Therefore, we believe that our model provides a significant insight into the development of the spinal nerve, which is valuable information for clinical medicine.